Hepatoprotective effect of tumour necrosis factor α blockade in psoriatic arthritis: a cross-sectional study. Issue 6 (22nd October 2009) - Seitz, Michael; Reichenbach, Stephan; Möller, Burkhard; Zwahlen, Marcel; Villiger, Peter M; Dufour, Jean-Francois
Abstract : Objective: To evaluate the impact of tumour necrosis factor α (TNFα) blockers on the presence of liver fibrosis in patients with rheumatoid arthritis (RA) and psoriatic arthritis (PsA) treated with methotrexate (MTX). Methods: Participants were consecutive patients with RA and PsA who had undergone MTX treatment for at least 1 year ± TNF blockade for over 6 months. Liver fibrosis was assessed using non-invasive transient elastography (FibroScan). Regression models were used to compare FibroScan values of patients with RA and patients with PsA receiving TNFα blockers with those who were not. Results: FibroScan assessments were performed on 51 patients with RA and 43 patients with PsA. Compared to patients with RA, those with PsA were predominantly young men, received lower cumulative dosages of MTX and exhibited a higher incidence of liver steatosis and hyperlipidaemia. An abnormal result was observed in 7.1% of the anti-TNFα-naïve and in 13% of the anti-TNFα-treated patients in the RA group and in 30% of the anti-TNFα-naïve and 4.3% of the anti-TNFα-treated patients in the PsA group (OR=0.11, 95% CI 0.02 to 0.98). Results of the PsA group were robust when adjusted for baseline characteristics. Conclusion: The results suggest a protective effect of TNFα inhibitors against the development of liver fibrosis in patients with PsA.